The Model of Friendly Work Environment for Older Employees in Slovenia - Vesna Čančer; Maja Rožman (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
In the context of demographic changes and active aging in the workplace, managing age diversity contributes to creating new perspectives across the entire field of human resource management. The main objective of this paper is to determine the impact of appropriate working conditions and training programs for older employees on the work motivation of older employees, as well as to determine the impact of work motivation on the work engagement of older employees in Slovenia. In the medium-sized and large companies that were involved in the research, we surveyed employers and older employees: in the questionnaire, employers indicated their agreement to the listed statements about appropriate working conditions and training programs for older employees, and older employees indicated their agreement to the listed statements about work motivation and work engagement. Structural equation modelling has been proven useful in exploring the links between these four constructs. Results show that appropriate working conditions and training programs for older employees have a positive impact on the work motivation of older employees and that the work motivation of older employees has a positive impact on the work engagement of older employees.
Keywords: J24; I19; C38; 330; friendly work environment; older employees; structural equation modeling